ESTIMASI KEBUTUHAN MATERIAL PADA PERKERJAAN REPARASI DI PT. MULTI OCEAN SHIPYARD - Tyas Adi, Fajar; Saputra; Dasira, Alyuan; Zaki Prawira, Muhammad; Pradana Putra, Andrew (JURNAL JALASENA, 2024)
Material Needs Estimation The plate used in the ship repair process is a major requirement of raw material supporting the shipping industry. We know that the amount of material is never right in a development, which often happens to be inadequate and has an impact on the disruption of a production process. The situation is inadequate to a need that the production process is obstructed or runs smoothly, excessive raw material procurement can cause high storage costs and investment in raw material supplies. Material is a construction project that covers 40-60% of the cost to be issued by the company. In this paper, an analysis of the material needs of PT. Multi Ocean Shipyard. So get results for MT. FORTUNE PASIFIC-XLIX can be known as ton of 20354.3kg. To reduce the set-up, and lead time costs and maximize operational efficiency and also inventory investment can be suppressed as low as possible. By using the MRP (Material Requirement Planning) method, it is possible to calculate the amount, cost and time of the MRP Form to know the order, volume and tonnage time. Keywords: Material Management, MRP, Ship Repair, Management System